Reconhecimento e ressignificação : identidade positiva e juventude negra - Natália de Oliveira Tavares (2014)
The objective of this paper is to investigate and understand how afro-Brazilians build their racial identities, restrained by different personal experiences and social conflicts, in the midst of sociocultural and institutional processes in a society that value a social hierarchy in which the white people has a superior position. Thus, this research sought to identify, from semistructured interviews (with young people who declare themselves as black or afro-Brazilian) which sociocultural and subjective elements (present in their speech) affect and encourage such positive identity perception, identification and affirmation. This positive identity that surpasses the idea of white superiority preached through the stealthy prejudice and racism in our country and that put forward the recognition and appreciation of the black people and their culture. This study was motivated by the necessity of thinking this positive construction of identity in black young people that overcome the myths and prejudices transmitted among every area of our society. This construction of identity was investigated through a specific event, which triggers racial perception, reflection and acceptance and the possible resonances in these subjects lives. For the interpretations of the narratives it was used the content analysis. Besides expanding the theoretical material on this speech inside the Psychology field, we intend to contribute to the life improving of the black people, working as theoretical support for creation and implementation of public politics and social actions, that help the human rights promotion, the strengthening of the black people identity and the recognition of this population.